2013
DOI: 10.2147/ppa.s45471
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in dialysis patients with constipation: a cross-sectional study

Abstract: ObjectivesTo evaluate differences in the health-related quality of life (HRQoL) between patients with constipation receiving hemodialysis (HD) and those receiving peritoneal dialysis (PD).MethodsIn this cross-sectional study, 605 dialysis patients (478 HD cases and 127 PD cases; all patients were older than 18 years) from our hospital were included. A questionnaire was used to evaluate their constipation statuses. The effect of constipation on HRQoL was assessed, using the Chinese version of the 12-item short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…We have demonstrated that FC is independently associated with BP and VT, parts of SF-36v2 physical and mental summary components, respectively. Similarly, Zhang et al have shown that FC is associated with lower scores in both physical and mental summary components of HRQoL in both HD and PD patients 17 . Interestingly, our study has indicated that constipation diagnosed with BSFS is not associated with worse HRQoL in conservatively-treated CKD patients.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have demonstrated that FC is independently associated with BP and VT, parts of SF-36v2 physical and mental summary components, respectively. Similarly, Zhang et al have shown that FC is associated with lower scores in both physical and mental summary components of HRQoL in both HD and PD patients 17 . Interestingly, our study has indicated that constipation diagnosed with BSFS is not associated with worse HRQoL in conservatively-treated CKD patients.…”
Section: Discussionmentioning
confidence: 83%
“…Among all GI symptoms, constipation is the most frequently assessed GI symptom in dialysis patients, and the prevalence of constipation is higher in hemodialysis (HD) patient than in peritoneal dialysis (PD) patients (23.8-71.7% vs 14.2-28.9% of patients, respectively) 16 . In dialysis patients, like in a general population, constipation is associated with worse HRQoL 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The full texts of the remaining 80 articles were retrieved and assessed for eligibility. A total of 35 articles were excluded for the following reasons: comparison group other than in-center HD, 48 , 49 , 50 groups were not separately presented, 51 , 52 , 53 , 54 , 55 unspecified HRQoL questionnaire, 56 , 57 , 58 , 59 HRQoL data exclusively presented in graphs, 60 , 61 , 62 unclear calculation of HRQoL scores, 63 , 64 and outdated population data (data collected before 2007). 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 The studies of Garg et al 17 (Frequent Hemodialysis Network trials) and Jardine et al 81 (ACTIVE dialysis trial) were excluded because they focused on frequent HD that was not exclusively performed at home.…”
Section: Resultsmentioning
confidence: 99%
“…27 Insoluble fiber supplementation and its laxation effect may be of significant benefit to those in later stages CKD, particularly those on dialysis. 28 No further increase in stool frequency was observed with inulin supplementation. Although increased stool frequency has been reported with inulin 29 and oligofructose, 30 the expected increase would be small and likely masked by the significant effect of the pea hull fiber.…”
Section: Discussionmentioning
confidence: 96%